The Influence of Green Products and Service Quality on Consumer Satisfaction - Saut Rediman Situmorang; Manalu, Herold Moody; Hutabarat, Francis (Jurnal Multidisiplin Sahombu, 2025)
This study examines the influence of environmentally friendly products (green products) and service quality on customer satisfaction at vegan restaurants in Cicendo District, Bandung City. Using a quantitative approach with survey data from 135 respondents, the results show that green products significantly affect customer satisfaction (t = 4.72; p < 0.05), while service quality also has a significant effect (t = 5.31; p < 0.05). Simultaneously, both variables contribute positively (F = 28.45; p < 0.05), indicating that eco-friendly products enhance consumer perceptions of sustainability, and service quality improves overall customer experience. The findings suggest that innovation in green products and service quality improvement through employee training and consumer education are essential strategies to strengthen the competitiveness of vegan restaurants.